Once-Weekly Oral Dosing of MK-8591 Protects Male Rhesus Macaques From Intrarectal Challenge With SHIV109CP3. (8th June 2019) - Markowitz, Martin; Gettie, Agegnehu; St. Bernard, Leslie; Andrews, Chasity D; Mohri, Hiroshi; Horowitz, Amir; Grasperge, Brooke F; Blanchard, James L; Niu, Tao; Sun, Li; Fillgrove, Kerry; Hazuda, Daria J; et al.
Abstract: Background: MK-8591 (4′-ethynyl-2-fluoro-2′-deoxyadenosine [EFdA]) is a novel reverse transcriptase–translocation inhibitor. Methods: We assessed MK-8591 as preexposure prophylaxis in the rhesus macaque model of intrarectal challenge with simian/human immunodeficiency virus (SHIV). In study 1, 8 rhesus macaques received 3.9 mg/kg of MK-8591 orally on day 0 and once weekly for the next 14 weeks. Eight controls were treated with vehicle. All rhesus macaques were challenged with SHIV109CP3 on day 6 and weekly for up to 12 challenges or until infection was confirmed. The dose of MK-8591 was reduced to 1.3 and 0.43 mg/kg/week in study 2 and further to 0.1 and 0.025 mg/kg/week in study 3. In studies 2 and 3, each dose was given up to 6 times once weekly, and animals were challenged 4 times once weekly with SHIV109CP3. Results: Control macaques were infected after a median of 1 challenge (range, 1–4 challenges). All treated animals in studies 1 and 2 were protected, consistent with a 41.5-fold lower risk of infection ( P < .0001, by the log-rank test). In study 3, at a 0.1-mg/kg dose, 2 rhesus macaques became infected, consistent with a 7.2-fold lower risk of infection ( P = .0003, by the log-rank test). The 0.025-mg/kg dose offered no protection. Conclusions: These data support MK-8591's potential as a preexposure prophylaxis agent. Abstract : MK-8591 (also known as "EFdA") prevents simian/human immunodeficiency virus (SHIV) infection in the rhesus macaque model of intrarectal SHIV challenge when administered orally once weekly in increasingly decreased doses, demonstrating its potential for low-dose, extended-duration prophylaxis against HIV infection.